A wideband metamaterial absorber based on multiple interference model for mid-infrared applications - Nilotpal; Bhattacharyya S.; Chakrabarti P. (My University, 2025)
An ultrathin wideband metamaterial absorber based on multiple reflection interference model has been reported in this paper. The structure exhibits more than 95% absorption in the mid-infrared region extending from 5.6 μm to 7.1 μm. The absorption mechanism has been demonstrated based on the formation of Fabry-Perot resonance inside the dielectric cavity. The amplitude and phase conditions required for minimum reflection and maximum absorption in the entire band of operation has been well demonstrated in this paper. The structure exhibits wideband absorptivity response by maintaining size compactness (λ/5) and ultra-Thin property (λ/24). © 2020 Indian Radio Science Society.